Revolution : interior design from 1950 - Plunkett, Drew (London : RIBA Publishing, 2016)
"The last half of the twentieth century saw the emergence, evolution and consolidation of a distinct interior design practice and profession. This book is invaluable for students and practitioners, providing a detailed specialist, contemporary historical analysis of their profession and is beautifully illustrated, with over 200 photos and images from the 1950s through to the present day."--Cover.
In the beginning : 1945-55 -- The times they were a-changin' : 1956-68 -- Anxieties and allusions -- Grim down south -- Big bang -- Big beasts -- The next generation -- Shopping gets serious -- And AR begat DJ -- Storms in teacups -- To the 1990s and beyond -- Education lite -- All change -- Onward and inward.
Includes bibliographical references and index.
ARC
Trim Education
Keywords: Interior decoration -- History -- 20th century; Interior decoration -- History -- 21st century; Interior architecture -- History -- 20th century; House and Home; Interior architecture; Architecture